Gender-related differences in post-discharge bleeding among patients with acute coronary syndrome on dual antiplatelet therapy: A BleeMACS sub-study. Issue 168 (August 2018) - Grodecki, Kajetan; Huczek, Zenon; Scisło, Piotr; Kowara, Michał; Raposeiras-Roubín, Sergio; D'Ascenzo, Fabrizio; Abu-Assi, Emad; Henriques, Jose Paulo Simao; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B.; Kikkert, Wouter J.; et al.
Abstract: Introduction: Bleeding is an independent risk factor of mortality in patients with acute coronary syndromes (ACS). BleeMACS project focuses on long-term bleeding events after hospital discharge, thus we evaluated gender-related differences in post-discharge bleeding among patients with ACS. Materials and methods: We investigated 13, 727 ACS patients treated with percutaneous coronary intervention and discharged on dual antiplatelet therapy (either with clopidogrel or prasugrel/ticagrelor). Endpoint was defined as intracranial bleeding or any other bleeding leading to hospitalization and/or red blood transfusion. Results: Post-discharge bleeding was reported more frequently in females as compared with males (3.7% vs. 2.7%, log-rank P = 0.001). Females ( n = 3165, 23%) were older compared to men (69.0 vs. 61.5 years, P < 0.001) and with more comorbidities. Hence, in multivariate analysis female sex was not identified as an independent risk factor of bleeding (HR 1.012, CI 0.805 to 1.274, P = 0.816). Administration of newer antiplatelet agents compared to clopidogrel was associated with over twofold greater bleeding rate in females (7.3% vs. 3.5%, log-rank P = 0.004), but not in males (2.6% vs. 2.7%, log-rank P = 0.887). Differences among females remained significant after propensity score matching (7.2% vs 2.4%, log-rank P = 0.020) and multivariate analysis confirmed that newer antiplatelet agents are independent risk factor for bleeding only in women (HR 2.775, CI 1.613 to 4.774, P < 0.001). Conclusions: Bleeding events occurred more frequently in women, but female sex itself was not independent risk factor. Administration of newer antiplatelet agents was identified as independent risk factor of bleeding after hospital discharge in female gender, but not in male patients. Highlights: Bleeding events are more frequent in women treated for acute coronary syndromes than in men. Female sex is not an independent risk factor of post-discharge bleeding after acute coronary syndromes. Newer antiplatelet agents increase risk of post-discharge bleeding in women, but not in male patients.